Personalization in Marketing: Effectiveness and Challenges - Dewi Indriani Jusuf (Paspama Institute, 2023)
Personalization has become a major focus in modern marketing strategies to achieve deeper consumer engagement and increased response rates. This research aims to investigate the effectiveness of using personalization in marketing strategies and to identify the main challenges faced by companies in implementing this personalization approach. This research method is descriptive qualitative with data collection through literature reviews. The research results show that personalized marketing has proven effective in increasing customer engagement, improving customer experience, and increasing sales conversions for companies. However, challenges such as privacy protection and data security, complex data management, the risk of overpersonalization, and resource and technology limitations need to be overcome so that personalized marketing strategies can be implemented optimally. By overcoming these challenges, companies can harness the potential of personalized marketing to build more intimate relationships with customers, strengthen loyalty and improve brand positioning in the marketplace.